Editorial - González-Campo, Carlos Hernán (Cuadernos de Administración, 2017)
The 58th issue of 2017 is the product of an open summons of papers carried out within the national and international scientific community, which makes part of the journal’s publishing strategy for the years to come; this an electronic issue and in English that seeks greater divulgation of scientific knowledge in the area. These papers resumes quite relevant discussions Corporate Social Responsibility, patients’ loyalty, the usage of management tools in SMEs, territorial planning or the role of companies in peace-building.The first paper of this issue bears the title “Correlational study of the factors that influence in the recommendation and loyalty of patients of aesthetic medicine, Medellin, Colombia 2014”, where with a sample of 391 patients from Medellin´s (Colombia) metropolitan area the authors identify the factors that influence processes of recommendation and loyalty produced within the medic-patient relationship in aesthetic medicine, and seek to find relations within these factors by using statistical methods.Forecasting in the industrial SMEs of Ibague: variables that determine their application is the second paper from this issue, where by means of both qualitative and quantitative analysis is proposed a research on variables that determine the practice of forecasting in small and medium-sized industrial companies from Ibague, Tolima, Colombia. The paper presents this research’s results, which determine the relationship among the proposed attributes and the use of this kind of techniques in the managing of said companies.The third paper is “Corporate Social Responsibility and pro-Peace practices in Colombia”, which poses the relationship between the adoption of Corporate Social Responsibility models and implementing Pro-Peace practices in scenarios of conflict and post-conflict. By using qualitative methods it was found that if companies in Colombia wish to promote peace they must become involved in management models based on Corporate Social Responsibility. Corporate Social Responsibility and peace-building: analysis of a Colombian multinational is the title borne by the fourth paper, where the authors present the results stemming from a research based on sustainability reports corresponding to the 2010-2015 period issued by a multinational operating in Colombia, and analyzed by means of grounded theory design.The fifth paper is Analysis of construction projects stakeholders from Corporate Social Responsibility, where an analysis of housing construction projects stakeholders is presented from a Corporate Social Responsibility approach, and based on the application of the Stakeholher Circle complimented by some risk management-related matrixes and the usage of the MicMac software from the structural analysis model. Among other conclusions is posed the importance of setting up actions and strategies for these stakeholders, due to them being implicated in optimizing the system from the setting up of permanent challenges given their high motoricity and high dependence.New approaches to planning and development: the case of Gramalote, Norte de Santander, Colombia is the sixth research paper from this journal’s 58th issue where the authors analyze the territorial planning from Gramalote, Norte de Santander, Colombia from the development planning or territorial development approaches, and their relationship with the 2010 disaster. From a qualitative and documentary approach were reviewed the municipality’s 2004-2017, 2008-2011 and 2012-2015 development plans. Among the results territorial planning is posed as having been carried out improperly before and after the 2010 disaster, due to the economic orientation thereof.Finally, this issue’s last paper is one of review by the name “Approaches and social perspectives of Corporate Responsibility” where the authors present the existing debates from different disciplines and perspectives about the Corporate Social Responsibility concept and its relationship, among others, with conceptual elements determinant of the company.As responsible for this publication I thank the authors of these papers for trusting our editorial process, clarifying that they are accountable for the content of each of their papers and the revising of the translations carried out in some cases. We hope this issue’s scientific content contributes to the knowledge from the different areas.